Germline genetic factors in the pathogenesis of myeloproliferative neoplasms. (July 2020) - Bellanné-Chantelot, Christine; Rabadan Moraes, Graciela; Schmaltz-Panneau, Barbara; Marty, Caroline; Vainchenker, William; Plo, Isabelle
Abstract: Myeloproliferative neoplasms (MPN) are clonal hematological malignancies that lead to overproduction of mature myeloid cells. They are due to acquired mutations in genes encoding for AK2, MPL and CALR that result in the activation of the cytokine receptor/JAK2 signaling pathway. In addition, it exists germline variants that can favor the initiation of the disease or may affect its phenotype. First, they can be common risk alleles, which correspond to frequent single nucleotide variants present in control population and that contribute to the development of either sporadic or familial MPN. Second, some variants predispose to the onset of MPN with a higher penetrance and lead to familial clustering of MPN. Finally, some extremely rare genetic variants can induce MPN-like hereditary disease. We will review these different subtypes of germline genetic variants and discuss how they impact the initiation and/or development of the MPN disease.